A Systematic Review and Meta-Analysis on the Real-World Effectiveness of COVID-19 Vaccines against Infection, Symptomatic and Severe COVID-19 Disease Caused by the Omicron Variant (B.1.1.529) - Hassen Mohammed; Dan Duy Pham-Tran; Zi Yi Michelle Yeoh; Bing Wang; Mark McMillan; Prabha H. Andraweera; Helen S. Marshall (Vaccines, 2023)
Real-world data on the effectiveness of COVID-19 vaccines against the Omicron variant (B.1.1.529) is limited. This systematic review aimed to investigate the real-world effectiveness and durability of protection conferred by primary course and booster vaccines against confirmed Omicron infection, and severe outcomes. We systematically searched literature up to 1 August 2022. Meta-analysis was performed with the DerSimonian-Laird random-effects model to estimate the pooled vaccine effectiveness (VE). Overall, 28 studies were included representing 11 million individuals. The pooled VE against Omicron infection was 20.4% (95%CI: 12.1–28.7%) and 23.4% (95%CI: 13.5–33.3%) against symptomatic infection with variation based on vaccine type and age groups. VE sharply declined from 28.1% (95%CI: 19.1–37.1%) at three months to 3.9% (95%CI: −24.8–32.7%) at six months. Similar trends were observed for symptomatic Omicron infection. A booster dose restored protection against Omicron infection up to 51.1% (95%CI: 43.8–58.3%) and 57.3% (95%CI: 54.0–60.5%) against symptomatic infection within three months; however, this waned to 32.8% (95%CI: 16.8–48.7%) within six months. VE against severe Omicron infection following the primary course was 63.6% (95%CI: 57.5–69.7%) at three months, decreased to 49% (95%CI: 35.7–63.4%) within six months, and increased to 86% after the first or second booster dose.